Evaluation of Neurosurgery Residency Training and Surgical Performance: A National Survey in Turkey - Turkmen, Tolga; Unluer, Caner; Deniz, Sahin Kenan; Kayhan, Ahmet; Cingoz, Ilker Deniz; Ozkeles, Yagmur Eylem; Kuzucu, Pelin (Turkish Neurosurgical Soc, 2025)
AIM: To assess the number of independent surgical procedures performed, working hours, and satisfaction with training among residents in Turkey. MATERIAL and METHODS: An electronic survey was sent to all neurosurgery residency in Turkey through e-mail and social media group. The survey, which includes 37 questions primaly encompassed independently performed surgical procedures, work hours (post-night shift rest), satisfaction of educational activities. RESULTS: The responses were collected from n=276 participants, representing 35% of the entire residents. Responses came from 88% (73/83) of all training programs in Turkey. The independent application more than fifteen rate for low-risk interventions (External ventricular drain (EVD) /intracranial pressure (ICP)-monitoring, supratentorial craniotomy, lumbar drainage, laminectomy) was approximately 50% in PGY 3 and 80% in PGY 4&5. %50 of PGY 4&5 residents performed more than fifteen procedures for hematoma, shunting, lumbar disc disease, and thoracic-lumbar (TL) trauma surgery. Post-night shift rest is implemented in the majority of training programs, with data revealing that it is statistically more widely adopted in training and research hospitals compared to other educational programs. 84% of responders found post-night shift rest beneficial. CONCLUSION: Post-night shift rest is implemented in the majority of training programs, and most residents find it beneficial. Only half of senior residents adequately apply general neurosurgery practices. However, it is predicted that resting after shifts could further shorten the overall training period and negatively impact the already low case numbers for residents. Therefore, it is crucial to organize and standardize training programs in a way that mitigates this negative effect. The fact that only a quarter of residents plan to practice their profession in Turkey raises serious concerns about the future sustainability of neurosurgical services at the national level.
Keywords: Working hour restriction; Neurosurgery Residency; Satisfaction rate; Independently performed case; Turkish Neurosurgical Society; Turkish Young Neurosurgeons Board